Implementasi Knowledge Management dan Analisis SWOT di Perpustakaan Perguruan Tinggi - Ida Mariani Pasaribu (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
The library college as academic library will continue to exist plays a role to play in the life of a college. The library college should be able to understand the concepts of Knowledge Management and make a SWOT analysis. The purpose of this paper is to describe the implementation of knowledge management and SWOT analysis in the University Library. The methods used for data by observation and internet resources, lectures and scientific journals. The results of this paper found that to achieve the implementation of knowledge management and SWOT analysis, therefore (1) The University Library is expected to: (a) Understand the concept of Knowledge Management (creation, recording and organization, deployment, access and use, and continued with the re-creation of knowledge, etc), (b) Partner for the user, (c) Serving an individual or group as a member of the network, (d) Provides Knowledge Management, (2) The leader of library capable elaborated with the potential and the skills possessed by the existing resources in the library, (3) Support of the policy makers, so that of Knowledge Management will impact to all activities of civitas academic in universities.